2017
DOI: 10.1016/j.appet.2016.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Social appearance anxiety and dietary restraint as mediators between perfectionism and binge eating: A six month three wave longitudinal study

Abstract: Binge eating is related to perfectionism and restrained eating. However, the mechanisms underlying these relationships are not well understood. It is possible that social anxiety, specifically social appearance anxiety (i.e., the fear of overall appearance evaluation), influences the relationship between binge eating, perfectionism, and dietary restraint. In the current study (N = 300 women), we tested the relationship between dietary restraint, social appearance anxiety, concern over mistakes (a component of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 67 publications
1
28
0
3
Order By: Relevance
“…The configuration of intensity for all measures confirms results often obtained by individuals in a healthy population (people who do not manifest various types of eating disorders), which also is reflected in research conducted by Boyd (2006) , who showed that compared to individuals suffering from eating disorders, healthy people show less disordered emotional functioning, higher ability to cope with negative emotions in stressful situations, better ability to cope with stress and lower level of psychopathological traits. Other studies have also indicated that psychopathological traits of excessive anxiety, depression, impulsivity, emotional dysregulation, and negative coping are important criteria that differentiate healthy people from those with eating disorders ( Grant et al, 2002 ; Jacobi et al, 2004 ; Boyd, 2006 ; Tchanturia et al, 2012 ; Torres et al, 2015 ; Gorwoord et al, 2016 ; Levinson and Rodebaugh, 2016 ; Brosof and Levinson, 2017 ; Wang and Li, 2017 ; Westwood et al, 2017 ; Brown et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The configuration of intensity for all measures confirms results often obtained by individuals in a healthy population (people who do not manifest various types of eating disorders), which also is reflected in research conducted by Boyd (2006) , who showed that compared to individuals suffering from eating disorders, healthy people show less disordered emotional functioning, higher ability to cope with negative emotions in stressful situations, better ability to cope with stress and lower level of psychopathological traits. Other studies have also indicated that psychopathological traits of excessive anxiety, depression, impulsivity, emotional dysregulation, and negative coping are important criteria that differentiate healthy people from those with eating disorders ( Grant et al, 2002 ; Jacobi et al, 2004 ; Boyd, 2006 ; Tchanturia et al, 2012 ; Torres et al, 2015 ; Gorwoord et al, 2016 ; Levinson and Rodebaugh, 2016 ; Brosof and Levinson, 2017 ; Wang and Li, 2017 ; Westwood et al, 2017 ; Brown et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that indicate that alexithymia may trigger unhealthy eating attitudes and be related to symptoms of eating disorders, thus strengthening anxiety, depression, and stress( Tchanturia et al, 2012 ; Torres et al, 2015 ; Westwood et al, 2017 ; Brown et al, 2018 ). There are also studies indicating a lack of evidence to support a significant role for affective disorders in the formation of unhealthy eating attitudes, thus suggesting possible multi-level correlations between improper eating and body attitudes in eating disorders and various affective disorders ( Wallis and Hetherington, 2009 ; Gorwoord et al, 2016 ; Levinson and Rodebaugh, 2016 ; Brosof and Levinson, 2017 ; Wang and Li, 2017 ). From psychological and medical perspectives, particularly in preventive healthcare and the prevention of eating disorders, seeking the unexplored multi-level influences of various psychosocial conditions on the formation of unhealthy eating attitudes is important for medical and psychological treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, social appearance anxiety has been found to be more strongly linked to EDs, such as anorexia and bulimia nervosa, relative to other facets of social anxiety (Dakanalis et al, 2016; Levinson and Rodebaugh, 2012; Levinson et al, 2013). Brosof and Levinson (2017) investigated 300 women, and found that social appearance anxiety not only predicted binge eating at baseline but also mediated the relationship between concern over mistakes and binge eating across 6 months.…”
Section: Theoretical Review and Research Hypothesesmentioning
confidence: 99%
“…Yapılan iki çalışmada da SYBDÖ'nin beslenme alt boyutu ile SGK arasında ilişki olmadığı saptanmıştır (16,19). Bununla birlikte literatür incelemesinde beslenme davranışı, obezite, aşırı yeme, bulimia nevroza gibi beslenme sorunları ile SGK arasındaki ilişkiye yönelik çalışmaların sıklıkla yapıldığı görülmektedir (26)(27)(28). Kılıç ve Karakuş (2016) üniversite öğrencileri ile yapmış olduğu çalışmada da kilosundan hiç memnun olmayanlarda SGKÖ puan ortalamasının daha yüksek olduğunu belirtmiştir (17).…”
Section: Araştırmanın Evren Ve öRneklemiunclassified